2017
DOI: 10.3390/e19020076
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Postural Stability during Upright Standing between Normal and Flatfooted Individuals, Based on COP-Based Measures

Abstract: Aging causes foot arches to collapse, possibly leading to foot deformities and falls. This paper proposes a set of measures involving an entropy-based method used for two groups of young adults with dissimilar foot arches to explore and quantize postural stability on a force plate in an upright position. Fifty-four healthy young adults aged 18-30 years participated in this study. These were categorized into two groups: normal (37 participants) and flatfooted (17 participants). We collected the center of pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Also Cote et al [27] reported that the actual structure of the foot affected overall postural stability, be that in static or dynamic conditions. Tahmasebi et al [28], and Chao et al [29], when comparing a group of the flat footed patients with the ones with the correctly arched feet, observed that there was an appreciable deterioration of overall postural stability in the flat footed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Also Cote et al [27] reported that the actual structure of the foot affected overall postural stability, be that in static or dynamic conditions. Tahmasebi et al [28], and Chao et al [29], when comparing a group of the flat footed patients with the ones with the correctly arched feet, observed that there was an appreciable deterioration of overall postural stability in the flat footed subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Jiang applied the MSE and MMSE approaches to analyze the gait function of 24 elderly, chronically ill patients with cardiovascular disease, diabetes mellitus, or osteoporosis [33]. Chao and Jiang based on COP-Based MMSE measures, further analysis to make a comparison of postural stability during upright standing between normal and flatfooted Individuals of 54 healthy young adults [34]. Their results showed that the MSE algorithms used to identify the sense of balance in young adults and elderly individuals were inferior to the MMSE algorithms utilized for the calculation of the CI of COP data.…”
Section: Multivariate Multiscale Entropy (Mmse)mentioning
confidence: 99%
“…In a study by Ahmadi et al, sample entropy (as an indicator of COP) was higher in participants who were walking while playing games than in participants who were only walking [ 16 ]. Chao et al used two nonlinear parameters, namely sample entropy and multivariate sample entropy, to compare the COP of individuals with regular feet and flat feet [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The data investigated in this article are from an open database developed by Santos et al [ 16 ]. Montesinos et al analyzed the same dataset and explored the various default parameters of approximate entropy and sample entropy relevant to these features [ 17 ]. However, there are few entropy features that are statistically significant between fall and non-fall groups of elderly subjects.…”
Section: Introductionmentioning
confidence: 99%